IMPACT OF TRAINING PROGRAM IN ADOPTION OF CATTLE FEED COMPUTATION BY FARMER INTEREST GROUPS (FIGs) OF TAMIL NADU - B. Rajesh Kumar; D. Baskaran; S. Saraswathi; C. Theophilus Anand Kumar (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A study was carried out to assess the impact of training program on adoption and opinion of the Farmer Interest Groups (FIGs) on cattle feed computation in Vellore district of Tamil Nadu. A total of twelve villages from twelve community development blocks were selected based on 17th livestock census of cattle population (2007), Tamil Nadu. Data were collected on pretested interview schedule. Training program was offered to 269 different village respondents on cattle feed computation and level of technology adoption was carried out to assess the effectiveness of the program through pre and post evaluation of respondents. Garrets Ranking Technique was performed in prioritizing the opinion of farmers on the new feeding technology pattern adopted by Farmer Interest Groups. The overall adoption percentage by the groups was 56.81%. Also the results clearly indicated that there was highly significant difference (P<0.01) in the knowledge level of the respondents before and after training. The Garrets Ranking technique revealed that the top score of 73.11 had been given to the cross bred animal which showed a marked increase in milk yield during the experimentation period of 15 days as adoption of new feeding technology and ranked the first position.